2007
DOI: 10.1002/ajp.20405
|View full text |Cite
|
Sign up to set email alerts
|

Ground use by northern muriquis (Brachyteles hypoxanthus)

Abstract: Many arboreal primates descend to the ground, a custom that may occur more frequently in disturbed habitats, and in the presence of researchers to whom the primates are habituated. In this paper, we describe opportunistic observations of ground use in two groups of northern muriquis (Brachyteles hypoxanthus) at the RPPN Feliciano Miguel Abdala, Minas Gerais, Brazil. Members of both groups were observed drinking, resting, feeding, playing, and traveling on the ground to different degrees, and variation in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 17 publications
2
44
2
7
Order By: Relevance
“…On the other hand, a low density of predators is thought to reduce primate alertness, which could at least partly explain the increased rate of non-essential activities (e.g. play) performed by arboreal northern muriquis (Brachyteles hypoxanthus) on the ground [Mourthé et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a low density of predators is thought to reduce primate alertness, which could at least partly explain the increased rate of non-essential activities (e.g. play) performed by arboreal northern muriquis (Brachyteles hypoxanthus) on the ground [Mourthé et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Marked terrestrial habits are present in some Catarrhini members such as Mandrillus, Papio and Macaca in the Old World. Observations of terrestrial behaviors were also reported for some essentially arboreal Neotropical primate species such as Alouatta, Cebus, Ateles and Brachyteles to obtain some food, water or minerals and/or for geographic dispersion (Dib et al, 1997;Emmons, 1999;Mandujano et al, 2004;Almeida Silva et al, 2005;Campbell et al, 2005;Mourthe et al, 2007;Pozo-Montuy & Serio-Silva, 2007). This last point is very important in fragmented forest habitats where monkeys move on the ground to reach new patches of forest but in so doing expose themselves to increased predation risks.…”
Section: Introductionmentioning
confidence: 90%
“…Mourthé et al (2007) propõem que a perturbação do habitat e a presença de pesquisadores parecem facilitar o uso do chão por muriquis-do-norte habituados na Reserva Particular do Patrimônio Natural Feliciano Miguel Abdala em Caratinga (MG), enquanto Tabacow et al (2009) sugerem que o comportamento desta população representa uma expansão de nicho em um habitat fragmentado, onde as oportunidades de dispersão são limitadas, facilitada por uma difusão da tradição entre os indivíduos. Ao redescobrirem o muriqui no PARNASO, Garcia e Andrade Filho (2002) relataram um "comportamento de enfrentamento" dos animais à presença dos pesquisadores, o que corrobora a ideia de que os primatas não estavam habituados a encontros com seres humanos nesta área altamente conservada (Castro, 2008).…”
Section: Paula Breves Austem Stravs Andrade Dias Alcides Pissinatti Junclassified